Activity of Tokulo (Kleinhovia hospita L.) as Anti Rheumatoid Arthritis and Anti-inflammatory in White Rats Induced by Complete Freud Adjuvant (CFA) - Fatma Sari Siharis; Selpirahmawati Saranani; Nurlansi Nurlansi (Journal of Tropical Pharmacy and Chemistry, 2021)
Tokulo (Kleinhovia hospita) leaves are commonly used by Moronene people (Southeast Sulawesi) to treat headaches. This is supported scientifically from research which states that tokulo leaves have analgesic and anti-inflammatory activity. The NSAID group is included in the anti-rheumatoid arthritis therapy. To determine the anti-RA activity of this plant, a study was carried out on CFA-induced rats. Based on the results of the study, it is known that the ethanol extract of tokulo leaves has anti-RA and anti-inflammatory activity in CFA-induced rats. Keywords: Kleinhovia hospita, Rheumatoid Arthritis, Inflammation